El Códice X o los anales del grupo de la Tira de la Peregrinación. Evolución pictográfica y problemas en su análisis interpretativo - María Castañeda de la Paz (Journal de la Société des Américanistes)
The Codex X or the Annals of the Tira de la Peregrinación Group. Pictographic Evolution and Problems in its Interpretative Analysis. Contact with the Spaniards meant the beginning of a process of transformation and change for the Mesoamerican writing tradition. Pictography was pushed to the background and was slowly substituted by alphabetic text, which initially was a mere register of the ancient oral discourse enclosed in the ancient codices. This process is manifested in a group of documents, all closely related pictorially and alphabetically, and which version of the Aztec-Mexitin migration – as we will see here – comes from a common source, the Codex X. However, the passing of time erased from the memory of the tlacuiloque much of the information that originated in the ancient pictorials. Thus were generated the problems of interpretation we are facing today.